2019
DOI: 10.1021/acs.biochem.9b00548
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of GDP-d-glycero-α-d-manno-heptose for the Capsular Polysaccharide of Campylobacter jejuni

Abstract: The capsular polysaccharide (CPS) structure of Campylobacter jejuni contributes to its robust fitness. Many strains contain heptose moieties in their CPS units. The precursor heptose is GDP-d-glycero-α-d-manno-heptose; modifications to the stereochemistry at C3–C6 as well as additions of methyl and phosphoramidate groups lend to the hypervariability of the C. jejuni CPS structures. Synthesis of GDP-d-glycero-α-d-manno-heptose has been described previously, but using enzymes from Aneurinibacillus thermoaerophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…These were dereplicated to 104 high and medium quality MAGs (>50% completeness and <10% contamination) following the MIMAG reporting standards [54]. In this study, we were able to retrieve a disproportionate number of high (32) and medium (72) draft quality MAGs compared to a recent study conducted in the SAO [52] (Supplementary Table 2). These MAGs represent the largest compendium of SAO genomes and comprised of taxonomically diverse archaeal (2) and bacterial (8) phyla (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…These were dereplicated to 104 high and medium quality MAGs (>50% completeness and <10% contamination) following the MIMAG reporting standards [54]. In this study, we were able to retrieve a disproportionate number of high (32) and medium (72) draft quality MAGs compared to a recent study conducted in the SAO [52] (Supplementary Table 2). These MAGs represent the largest compendium of SAO genomes and comprised of taxonomically diverse archaeal (2) and bacterial (8) phyla (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Of these genes, three had functional assignments to a liated sequences previously recovered from unclassi ed Phycodnaviridae which are known to infect algae in the Pyramimonas order [71]. gmhB catalyses two pathways that result in the production of precursors for the S-layer glycoprotein and Lipid A biosynthesis [70,72]. Previous studies have shown that microbial communities in low phosphorus environments use alternative P-recycling mechanisms [43,73].…”
Section: Euphotic Zone Viruses Encode Amgs That Potentially Reprogram Phosphorus Cyclingmentioning
confidence: 99%
“…ADP-heptose and other heptose metabolites are essential intermediates of the lipopolysaccharide heptose core biosynthetic pathway in all Gram-negative bacteria [12,14,[20][21][22][23] and can also be incorporated into bacterial surface layers [24,25] or produced by some Gram-positive bacteria [26]. Therefore, our results strongly suggest that the mechanism of adaptive immune response modulation and effects on antigen presentation based on this specific MAMP might also be adopted by other pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 83%
“…jejuni NCTC 11168 is composed of 35 genes, as illustrated in Figure S1 . Previous investigations have functionally characterized the genes necessary for the biosynthesis of the d -glycero- l -gluco-heptose moiety and modification (Cj1152, Cj1423, Cj1424, Cj1425, Cj1427, Cj1428, and Cj1430). In addition, the enzymes Cj1415, Cj1416, Cj1417, and Cj1418 have been shown to be required for the biosynthesis of the phosphoramidate modification, and gene knockout experiments have identified the enzymes (Cj1422 and Cj1421) required for the transfer of the phosphoramidate modifications to specific sugar receptors. , More recently, we have shown that Cj1441 is required for the conversion of uridine diphosphate (UDP)-glucose to UDP-glucuronate and that this enzyme is unable to catalyze the formation of an amide bond via the attack of an amine substrate with the putative thioester intermediate formed during the oxidation of UDP-glucose . The enzymes required for the biosynthesis of the two amines (serinol and ethanolamine) found in the HS:2 capsule are currently unknown.…”
Section: Introductionmentioning
confidence: 99%